Labilibacter sediminis sp. nov., isolated from marine sediment. Issue 1 (3rd February 2020) - Wang, Feng-Qing; Chen, Zhu-Jie; Yang, Jian-Min; Wang, Wei-Jun; Feng, Yan-Wei; Li, Zan; Sun, Guo-Hua
Abstract : A Gram-stain-negative, rod-shaped and facultatively anaerobic strain, designated CG51 T, was isolated from marine sediment collected from a coastal area in Weihai, PR China. Strain CG51 T grew at 4–37 °C (optimum, 28–30 °C), with 1.0–6.0 % (w/v) NaCl (2.0–3.0 %) and at pH 6.0–8.5 (pH 7.0–7.5). The predominant fatty acids were iso-C15 : 0, anteiso-C15 : 0 and iso-C14 : 0 . Major polar lipids included an unidentified lipid and a phospholipid. The respiratory quinone was MK-7 and the genomic DNA G+C content was 35.9 mol%. The results of phylogenetic analysis based on 16S rRNA gene sequences placed strain CG51 T in the genus Labilibacter with the close relatives being Labilibacter marinus Y11 T and Labilibacter aurantiacus HQYD1 T, exhibiting 96.5 and 96.3 % 16S rRNA pairwise similarity, values which are clearly below the 98.7 % threshold value recommended for species demarcation. Based on the phylogenetic, physiological, chemotaxonomic and genetic data, strain CG51 T represents a novel species within the genus Labilibacter, for which the name Labilibacter sediminis sp. nov. is proposed. The type strain is CG51 T (=MCCC 1K03739 T =JCM 33138 T ).